Risk factors for asthma exacerbation among Hajj pilgrims: a case study from DKI Jakarta, Indonesia (Medical Journal of Indonesia, 2020)
BACKGROUND Hajj pilgrims are prone to asthma exacerbation because of the high transmission rate of respiratory infections, severe environmental factors, and high-intensity activities during the Hajj. Well-controlled asthma status and preventive efforts prior to the Hajj could reduce such exacerbations. This research aimed to determine the risk factors of asthma exacerbation during the Hajj to help establish preventive measures. METHODS Participants were evaluated at community health centers (puskesmas) through history taking, physical examination, and spirometry. The risk factors examined included a history of exacerbation one year before the Hajj, obesity, comorbidities (e.g., diabetes mellitus, hypertension, coronary heart disease), lung function, smoking, fitness level, and influenza vaccination. Asthma exacerbation while in Saudi Arabia was determined through direct observations by authors and physicians assigned to Hajj pilgrim groups and analysis of data obtained from questionnaires distributed to the pilgrims before their departure. Odds ratios (OR) were calculated using logistic regression. RESULTS Among 68 pilgrims with asthma, exacerbation occurred in 27 (40%) pilgrims. Risk of asthma exacerbation was significantly increased in the pilgrims with a history of exacerbation one year before the Hajj (OR = 4.27; 95% confidence interval [CI] = 1.156–15.829; p = 0.029) and obesity grade II (OR = 4.02; 95% CI = 1.151–14.097; p = 0.029). Other factors, including smoking, comorbidities, lung function, fitness level, obesity grade I, and influenza vaccination, were not significantly related to exacerbation. CONCLUSIONS Obesity grade II and history of asthma exacerbation one year before the Hajj are strong factors for asthma exacerbation during Hajj pilgrims.